Identifying Influential Factors of the Patient Discharge Process from ShafaTakestan Hospital in Qazvin City - Parisa Rahmani; Rafat Mohebbifar; Sima Rafiei (Shahid Sadoughi University of Medical Sciences, 2020)
Background:The process of the patient discharge from the hospital is one of the most important processes that has been taken into consideration by managers in recent years. An efficient health system can only accomplish its duty to provide the health of the community by providing the right services and this system can be evaluated through its services. Therefore, the necessity of performing this research is to improve the quality of hospital services for patients and increasing patient satisfaction. This study has been aimed to identify the factors affecting the process of patient discharge. Methods: This was a cross-sectional study conducted in a general hospital located in Takestan, Qazvin in 2019. The study population in the qualitative section of the study included those who were aware of the discharge process and had managerial positions in the hospital. The sampling process was continued until achieving data saturation. The required information was gathered through reviewing relevant literature, observing the discharge process, and conducting semi-structured interviews with managerial members and study experts. Results:In the present study, the most important factors affecting the discharge process were lack of timely physician visit and issuance of the discharge order, delay in the approval of medication used by pharmacy officer, sending discharge files to hospital discharge unit, the patients' needs, diagnostic services (discharging with doctor's opinion), delays in registering nursing records, and undue secretarial performance in reviewing and recording reports in the hospital information system. Conclusion: The results of the present study, in line with other researches, have shown that the importance of the discharge process on hospital performance is undeniable and this process needs continuous investigation, monitoring, and intervention.